Revelation and the God of Israel - Samuelson, Norbert M., 1936- (Cambridge University Press, 2002)
Revelation and the God of Israel explores the concept of revelation as it emerges from the Hebrew Scriptures and is interpreted in Jewish philosophy and theology. The first part is a study in intellectual history that attempts to answer the question, what is the best possible understanding of revelation. The second part is a study in constructive theology and attempts to answer the question, is it reasonable to affirm belief in revelation. Here Norbert M. Samuelson focuses on the challenges given from a variety of contemporary academic disciplines, including evolutionary psychology, political ethics, analytic philosophy of religion, and source critical studies of the Bible. This important book offers a unique approach to theological questions and fresh solutions to them and will appeal to those interested in the history of philosophy, religious thought, and Judaism.